Politiikan vaikutus perustuslain tulkintaan – esimerkkinä lakien ennakollinen perustuslainmukaisuuden valvonta perustuslakivaliokunnassa - Dahlberg, Maija (Lakimies, 2024)
The influence of politics on constitutional interpretation – Ex ante constitutional review by the Constitutional Law Committee as an example In this article, I analyse the interplay between law and politics in ex ante constitutional review in Finland. I use the Finnish ex ante non-judicial constitutional review as an example of a process in which the influence of politics on constitutional interpretations is an integral element. In this case, the body responsible for the constitutional review of forthcoming legislation is a parliamentary committee – the Constitutional Law Committee (CLC) – which consists of Members of Parliament. Interestingly, however, Finnish constitutional custom requires CLC members to base their interpretations on legal argumentation and set aside their political interests. In this article, I study empirically how law and politics interact in constitutional interpretations through a qualitative case study incorporating 49 semi-structured interviews with key actors involved in the work of the CLC. More precisely, I analyse how the distinction between law and politics is understood in constitutional interpretation by the key actors themselves, and whether constitutional interpretation entails features of both political and legal decision-making. In order to do so, I draw on interviews with (a) MPs who have worked in the CLC, (b) secretaries of the CLC, and (c) legal experts who have acted as external advisors to the CLC.